2018
DOI: 10.1051/e3sconf/20183111001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Value Congruence, Brand Distinctiveness, Brand Social, Brand Warmth, and Memorable Brand Experience on Customer-Brand Identification and Brand Loyalty (Case Study: Brand of ACER Laptop)

Abstract: This study has several purposes. First, this study aims to investigate the effect of consumer–brand value congruence, brand distinctiveness, brand social benefit, brand warmth, and memorable brand experience on customer-brand identification (CBI). We call all of those factors as the antecedent factor of CBI. Second, this study aims to investigate the effect of CBI on customer loyalty. Third, investigate the role of product involvement as a moderating variable of the relationship between brand distinctiveness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…Concerning the impact of brand distinctiveness on brand awareness/associations, perceived quality and brand loyalty, it can influence these three dimensions in different ways. In particular, it can play a key role in helping consumers to identify a specific brand among other ones easily, thus enhancing the brand awareness and contributing to building specific consumers' associations toward it (Susanty and Tresnaningrum, 2018). At once, brand distinctiveness can also influence the brands' quality perceived by consumers.…”
Section: Brand Distinctiveness and Brand Equity Dimensionsmentioning
confidence: 99%
“…Concerning the impact of brand distinctiveness on brand awareness/associations, perceived quality and brand loyalty, it can influence these three dimensions in different ways. In particular, it can play a key role in helping consumers to identify a specific brand among other ones easily, thus enhancing the brand awareness and contributing to building specific consumers' associations toward it (Susanty and Tresnaningrum, 2018). At once, brand distinctiveness can also influence the brands' quality perceived by consumers.…”
Section: Brand Distinctiveness and Brand Equity Dimensionsmentioning
confidence: 99%
“…Brand distinctiveness refers to the need to uniqueness (Stokburger-Sauer et al, 2012). Susanty and Tresnaningrum (2018) define brand distinctiveness as "the pursuit of individual difference to others through the acquisition, use, and distribution of products to develop and reinforce individual and social identity". Yoo et al (2000) identified brand distinctiveness as the product of the highest level of brand awareness and distinctiveness in the customer's mind.…”
Section: Literature Review and Conceptual Framework 21 Brand Identitymentioning
confidence: 99%
“…Brand distinctiveness refers to the need to be unique and to create brand distinctiveness from both the customer and the marketer (Romaniuk et al, 2007). For a number of reasons, such as helping the customer identify the brand, providing effective customer relationships, reducing customer cognitive effort and helping to identify the brand easily among other brands, brand distinctiveness is important (Susanty and Tresnaningrum, 2018).…”
Section: Literature Review and Conceptual Framework 21 Brand Identitymentioning
confidence: 99%
“…For example, Alsem, Wieringa, and Hendriks (2007) show that values have an effect on the type of newspaper people choose, and Zhang and Bloemer (2008) find that values positively influence satisfaction, trust, affective commitment, and loyalty toward clothing store and bank brands. While a small number of other marketing-related studies (e.g., Allen, 2002;Lorgnier, Chanavat, Su & O'Rourke, 2020;Shokri & Alavi, 2019;Susanty & Tresnaningrum, 2018) also focus on the effects that values have on buying behavior they often limit themselves to one product category, do not compare the effect of values with that of functional attributes or brand personality, do not distinguish between products that people use for shorter periods of time such as a soft drink or for longer periods of time such as a car, nor do they distinguish between the effect of self-transcendence, which seems so important for values-driven brands, versus self-enhancement values .…”
Section: Introduction Of the Topicmentioning
confidence: 99%
“…Jonsen et al (2015) further support the importance of values-based positioning; they demonstrate that a focus on human values increases financial returns for companies. However, the marketing and brand literature rarely focuses on the effects of congruence between a consumer's values and a brand's values (Alsem et al, 2007;Elbedweihy et al, 2016;Lorgnier et al, 2019;Shokri and Alavi, 2019;Sihvonen, 2019;Susanty and Tresnaningrum, 2018;van Esterik-Plasmeijer and van Raaij, 2017;Zhang and Bloemer, 2008).…”
Section: Introductionmentioning
confidence: 99%